Sliding beamforming for target detection in the presence of a strong jamming. Issue 24 (3rd November 2020) - Li, Linna; He, Jin
Abstract : In this Letter, a new beamforming technique called sliding beamforming is proposed for target detection when a strong jamming signal is present. The basic philosophy of the sliding beamforming is to repeat an antenna‐pair beamformer in a sliding manner across the array to completely eliminate the jamming signal while preserving the gain of the array. For uniform linear antenna arrays, only a single beamformer weight is required so that the sliding beamforming has very low implementation complexity. Moreover, the sliding beamforming is also effective to handle the case that the jamming is in the array mainlobe. Output signal‐to‐interference‐plus‐noise ratio of the sliding beamformer is studied. A radar target detection example using the sliding beamforming is presented as well.